Pengembangan Komik Sejarah Islam dalam Meningkatkan Karakter Peserta Didik di SDN 13 Tigo Jangko Lintau Buo Kabupaten Tanah Datar - Arif Budiman; Nur Azizah Lubis (IAIN Batusangkar, 2022)
One media to help students develop their character is comics. The use of comics as media in the subject of Islamic Education at SD Negeri 13 Tigo Jangko Lintau Buo is not optimal. The contributing factor is the tendency to teach using conventional and very monotonous methods. The purpose of the study is to develop a valid and practical character-based Islamic historical comic to be used at the elementary school. The method in this study was Research and Development (R&D). In this study, there are 2 types of data, namely qualitative and quantitative data. The instruments to collect qualitative data were interview and observation guidelines. Meanwhile, the quantitative instruments were validity and practicality sheet. Using simple random sampling, the researcher took 10 fifth grade students at SDN 13 Tigo Jangko, Lintau Buo District, Tanah Datar Regency as the sample of this study. The results showed that the comics of Islamic history were valid in terms of purpose, rationale, content, characteristics, suitability, language, and design. Inserting characters in the comics were practical in terms of the ease of using the comics by students. The practicality of using comics was around 92%. The use of Islamic historical comics in improving the character of students was highly valid and practical, thus making students understand faster and can be directly practiced in their daily life, both at school and at home